Sandstone petrography and provenance of the Chubut Group (Cretaceous) in the Cañadón Matasiete (Golfo San Jorge Basin, central Patagonia): Implications for basin evolution and alluvial organization - Olazábal, Sabrina X. (2020)
Fil: Olazábal, Sabrina X. Universidad Nacional de la Patagonia San Juan Bosco. Departamento de Geología, FCNyCS. Chubut, Argentina.